Assessing efficiency of dairy goat farms by performance evaluation and benchmarking - Batzios, A; Theodoridis, A; Bournaris, T; Semos, A (Journal of the Hellenic Veterinary Medical Society, 2022)
The efficiency of goat farming sector in Greece is analyzed in this study. A survey was carried out in 96 goat farms, randomly selected in the area of Macedonia and Thrace, Greece. Accounting data were recorded through face-to-face interviews with farmers and Data Envelopment Analysis was applied to estimate technical efficiency (TE) of goat farms. The mean TE estimated at 0.791, indicating that input savings of 20.9% could be achieved. 75% of the goat farms are deemed as inefficient. The gross revenue varies considerably between efficient and inefficient farms, with the first achieving €210.09 and inefficient farms €143.41/doe. Farm size classification reveals significant difference of TE among groups of small and medium sized farms (P≤0.05). The analysis of the existing structure of the farms, compared to the optimal plan resulted from DEA, shows that farms could achieve higher economic results, through a rational use of the available inputs.